Malvern (1941) as a pioneering venture in Christian Ecotheology - Pihkala, Panu (Journal of beliefs and values, 2016)
The 1941 Malvern Conference included significant environmental statements, which have gradually been forgotten. In this article I point out their relevance and discuss their possible influence. I analyse the background of these environmental statements and suggest that British theology has probably played a stronger role in environmentalism than has previously been understood. I analyse the ecotheological positions of Malvern and William Temple in the context of a typology of ecotheological stances as developed by Willis Jenkins. While the exact influence of Malvern is difficult to assess, I refer to sources which show that its environmental content was noticed by certain prominent thinkers and contributed, for its part, to the development of ecumenical ecotheology.